Research on Factors Affecting Customers' Shopping Behavior on E-Commerce Exchanges during the Covid-19 Pandemic - Le Tan, Trinh; Hieu, Phan Thanh; Van, Nguyen Thi Thao; Linh, Do Thuy; Hung, Nguyen Nguyen Phuc; Duyen, Do Thi My (International Journal of Business, Management and Economics, 2021)
The article’s objective was to investigate the factors that affected customers' shopping behavior on e-commerce exchanges during the COVID-19 pandemic in Da Nang city. During the pandemic, in-store purchases are extremely difficult, and further research into e-commerce issues will attract more customers to online stores, and e-commerce platforms will become more common. Because of this, research is being conducted in order to address the aforementioned issues. In our research, we utilize qualitative research to build up hypotheses. A structured questionnaire with five-point Likert scales was distributed among 203 participants in Da Nang city (students, housewives, freelance businessmen) in order to collect data for the quantitative research The analysis technique, first is to test the reliability and validity of the instrument used, then the EFA discovery factor analysis, Pearson correlation and multiple regression analysis are performed. The research reveals that four variables influence buying on e-commerce exchanges: Payment method, Convenience, Trust factor, and Product variety, in which Payment method having the most impact. The study is important for e-commerce firms to improve their sales strategies in order to better fulfill the demands of their customers throughout the Covid-19 pandemic.